WEARING NIQAB BY MUSLIM WOMEN IS A DIVINE ORDER, RELIGIOUS FREEDOM AND A SUPERIOR MUSLIM CULTURE - Shafiqul Islam; Muhammad Musharraf Hussain; Nasrin Akter Chowdhury; Amani Ali Elmetwally; Hanif Suhairi Abu Bakar (Journal of Islamic, Social, Economics and Development, 2020)
One of the most significant events in the Muslim world is Islamic communication that intertwined same religious belief and culture. The purpose of the research is to reveal the rights of women in the society, which have significantly changed over the last few decades. It is observed that women possessing feminist sentiments are becoming more aggressive in some religious communities compared to women who accept their prescribed religious values as part of their normal religious freedom. This trend is creating a huge social impact in relation to practicing women’s individual’s freedom of choice. Recently, the term ‘Niqab’ has become divisive and it is having controversial interpretations around the globe. Niqab wearing women are also facing serious problems due to some propaganda made by the social media. Many countries imposed limited restriction to this important Islamic culture and think that the Niqab is often imposed to women, which indicates fundamentalism. It is also wrongly seen as an offense to human values and dignity. In view of this development a phenomenological research has been conducted among a total 45 Muslim and non-Muslim female participants who have come from different nations but stayed in Malaysia for a considerable period of time to achieve their individual objectives. The findings revealed that most of the women wear Niqab as their personal choice and religious obligation. Recently the Niqab wearing Muslim women has become a human rights concern in several countries. In this context, the freedom of rights of the Muslim women to choose their dress ups according to their choice and dictates of Islam has been challenged and curtailed to some extent in the light of the rights of others. In this study, wearing Niqab as women's personal choice and religious injunctions in the context of Malaysia has been exclusively discussed.